Maqashid-Based Framework for Islamic Digital Economy Transformation in Indonesia - Agus Wahyudi; Abdurrohman Kasdi; Abu Choir (Share: Jurnal Ekonomi dan Keuangan Islam, 2026)
The global digital economic transformation is reshaping financial systems and compelling Islamic economics to adapt while preserving its foundational ethical principles. This study examines strategies for integrating Islamic economic values into Indonesia’s digital economy, focusing on challenges related to digital literacy, regulatory fragmentation, technological infrastructure, and the operationalization of maqashid al-sharia. A systematic literature review was conducted using a critical synthesis of peer-reviewed journal articles, books, and contemporary policy documents to map emerging patterns within Islamic digital finance discourse. The findings show that the digitalization of Islamic finance—particularly through fintech innovations and digital banking—has contributed significantly to financial inclusion and the expansion of halal MSMEs. Rather than treating challenges as isolated phenomena, this study integrates them into a maqashid-based evaluative framework and introduces the concept of “maqashid fragmentation” to describe the misalignment between ethical objectives, technological design, and regulatory structures in Islamic fintech ecosystems. The analysis further demonstrates that maqashid al-sharia can function as a normative and strategic framework that aligns digital efficiency with Islamic ethical imperatives. This study highlights that sustainable development of Islamic economics in the digital era requires coordinated collaboration among government, industry, and academia through a triple helix approach to strengthen literacy, improve regulatory coherence, and expand inclusive infrastructure. The main contribution lies in offering a conceptual roadmap that advances Islamic economics as a viable framework for equitable and sustainable development in the digital age. Kerangka Berbasis Maqashid untuk Transformasi Ekonomi Digital Islam di Indonesia. Transformasi ekonomi digital global telah mengubah struktur sistem keuangan dan mendorong ekonomi Islam untuk beradaptasi tanpa meninggalkan prinsip etika fundamentalnya. Penelitian ini bertujuan untuk menganalisis strategi integrasi nilai-nilai ekonomi Islam dalam ekonomi digital Indonesia, dengan menyoroti tantangan literasi digital, fragmentasi regulasi, infrastruktur teknologi, serta operasionalisasi maqashid syariah. Penelitian ini menggunakan metode systematic literature review melalui sintesis kritis terhadap artikel jurnal bereputasi, buku akademik, dan dokumen kebijakan terkini untuk memetakan perkembangan kajian ekonomi digital Islam. Hasil penelitian menunjukkan bahwa digitalisasi keuangan syariah, khususnya melalui inovasi fintech dan perbankan digital, telah berkontribusi signifikan terhadap perluasan inklusi keuangan serta penguatan UMKM halal. Alih-alih memandang tantangan secara terpisah, penelitian ini mengintegrasikan berbagai persoalan tersebut ke dalam kerangka evaluatif berbasis maqashid syariah serta memperkenalkan konsep “fragmentasi maqashid” untuk menggambarkan ketidaksesuaian antara tujuan etika Islam, desain teknologi, dan struktur regulasi dalam ekosistem fintech syariah. Lebih lanjut, maqashid syariah diposisikan sebagai kerangka normatif dan strategis yang mampu menyelaraskan efisiensi digital dengan nilai-nilai etika ekonomi Islam. Penelitian ini menegaskan bahwa pengembangan ekonomi Islam di era digital memerlukan kolaborasi terkoordinasi antara pemerintah, industri, dan akademisi melalui pendekatan triple helix untuk memperkuat literasi, menyempurnakan regulasi, dan membangun infrastruktur yang inklusif. Kontribusi utama penelitian ini terletak pada penyusunan peta jalan konseptual untuk memperkuat peran ekonomi Islam dalam mendukung pembangunan yang adil dan berkelanjutan di era digital